Once was lost : a novel - Zarr, Sara. (New York : Little, Brown, 2011)
As the tragedy of a missing girl enfolds in her small town, fifteen-year-old Samara, who feels emotionally abandoned by her parents, begins to question her faith.
English language and literature.
Keywords: Faith -- Fiction; Self-perception -- Fiction; Parent and child -- Fiction; Missing children -- Fiction